Peningkatkan Kemampuan Guru Menyusun Rpp Melalui In House Training - Sarno; Rahmat Mulyono (Syntax Literate, 2023)
The purpose of this research is, "How are the efforts of the Principal to improve the ability of teachers in preparing lesson plans through In House Training (IHT)". In House Training (IHT) is a training program that is held at the training participant's place or at school by optimizing the potentials that exist in the school, using the trainee's work equipment with relevant material and the problems being faced, so it is hoped that participants can more easily absorb and apply the material to solve and overcome the problems experienced and be able to directly improve the quality and performance. In House Training (IHT) is carried out to improve teacher performance in accordance with their field of work by utilizing the potential that exists in an organization or institution. The results of InHouse Training (IHT) in compiling lesson plans in cycle I were still low, the teacher's score percentage reached 53.63. It is still far from the target planned in the research of 80. Even though there are actually only two aspects that have not been filled in, the aspects that have been filled in are not complete. For this reason, the research was continued in cycle II with several improvements. After conducting In House Training (IHT) in cycle II, there was an increase in competence in preparing lesson plans, implementing learning, and implementing process assessments (preparation of lesson plans) in accordance with Permendiknas Number 41 of 2007. Of the three aspects that were the focus of InHouse Training (IHT), all teachers who were the subject of the study experienced an increase.